Sperm capacitation is associated with phosphorylation of the testis-specific radial spoke protein Rsph6a†. Issue 2 (15th September 2018) - Paudel, Bidur; Gervasi, María Gracia; Porambo, James; Caraballo, Diego A; Tourzani, Darya A; Mager, Jesse; Platt, Mark D; Salicioni, Ana María; Visconti, Pablo E
Abstract: Mammalian sperm undergo a series of biochemical and physiological changes collectively known as capacitation in order to acquire the ability to fertilize. Although the increase in phosphorylation associated with mouse sperm capacitation is well established, the identity of the proteins involved in this signaling cascade remains largely unknown. Tandem mass spectrometry (MS/MS) has been used to identify the exact sites of phosphorylation and to compare the relative extent of phosphorylation at these sites. In the present work, we find that a novel site of phosphorylation on a peptide derived from the radial spoke protein Rsph6a is more phosphorylated in capacitated mouse sperm. The Rsph6a gene has six exons, five of which are conserved during evolution in flagellated cells. The exon containing the capacitation-induced phosphorylation site was found exclusively in eutherian mammals. Transcript analyses revealed at least two different testis-specific splicing variants for Rsph6a.Rsph6a mRNA expression was restricted to spermatocytes. Using antibodies generated against the Rsph6a N-terminal domain, western blotting and immunofluorescence analyses indicated that the protein remains in mature sperm and localizes to the sperm flagellum. Consistent with its role in the axoneme, solubility analyses revealed that Rsph6 is attached to cytoskeletal structures. Based on previous studies in Chlamydomonas reinhardtii, we predict that Rsph6 participates in the interaction between the central pair of microtubules and the surrounding pairs. The findings that Rsph6a is more phosphorylated during capacitation and is predicted to function in axonemal localization make Rsph6a a candidate protein mediating signaling processes in the sperm flagellum. Abstract : A sequence corresponding to the N-terminal domain of the radial spoke protein Rsph6 was found phosphorylated in capacitated sperm. Rsph6 expression is a testis-specific gene. Rsph6 protein remains present in mature sperm, and is localized to the sperm flagellum.